Effect of orexin‐A on mitochondrial biogenesis, mitophagy and structure in HEK293‐APPSWE cell model of Alzheimer's disease. (21st January 2021) - Zhu, Zhengyu; Xu, LinLin; Cao, DeYan; Song, ChaoYuan; Wang, YuZhen; Li, Maoyu; Yan, Jieke; Xie, ZhaoHong
Abstract: Mitochondrial dysfunction plays a key role in the pathogenesis and progression of Alzheimer's Disease (AD). Our previous studies showed that over expression of AD‐associated mutant β‐amyloid precursor protein (APP) led to abnormalities of mitochondrial biogenesis and mitophagy, leading to mitochondrial dysfunction. However, the mechanism remains unclear. In this study, we investigated the effect of orexin‐A on mitochondrial biogenesis, mitophagy and mitochondrial structure in overexpression of AD‐associated mutant APP cells. We used 20E2 cells as the AD cell model. 20E2 cells were treated with orexin‐A (50, 100 nmol/L). The effect of different concentrations of orexin‐A on cell activity was detected by MTT. As compared with the non‐treated 20E2 cells, orexin‐A‐treated 20E2 cells showed increased expression of APP, decreased cell viability and decreased adenosine triphosphate (ATP) level, decreased levels of regulatory proteins of mitochondrial biogenesis (peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha [PGC‐1α], nuclear respiratory factor 1/2 [NRF1/2], mitochondrial transcription factor A [TFAM]), increased levels of regulatory proteins of mitophagy (Parkin, PTEN‐induced putative kinase 1 [PINK1], microtubule‐associated protein light chain 3 II/I [LC3‐II/LC3‐I]) and decreased p62 level, with damaged mitochondrial structure. Orexin‐A may reduce mitochondrial biogenesis, enhance mitophagy and damage mitochondrial structure in AD. Abstract : In this study, we investigated the effect of orexin‐A on mitochondrial biogenesis, mitophagy and mitochondrial structure in the 20E2 (HEK293‐APPswe transgenic) cell model of AD. We prove that the 20E2 cell used in our experiment can be a successful cell model of AD. Cell viability was measured by the MTT assay. ATP Determination Kit was used to measure the ATP level. The regulatory protein of mitochondrial biogenesis and mitophagy were detected by western blot analysis. Transmission electron microscopy was used to observe mitochondrial structure. Orexin‐A may reduce mitochondrial biogenesis, enhance mitophagy and damage mitochondrial structure in the 20E2 cell model of AD.